GAMBARAN PENGETAHUAN MASYARAKAT TENTANG PENGELOLAHAN AIR BERSIH DI PULAU MAHENGETANG - Fernanda Tasya Sasuwe; Melky Pangemanan; Jilly Toar (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Background: Water is a fundamental necessity for all living beings. It is essential for humans not only as a raw material but also as a medium for production, for irrigation in agricultural activities, and as a resource for industrial production and electricity generation. The water available on Earth is crucial not only for humans but also for nature to maintain the stability of its ecosystem. Methodology: This study employs a descriptive analytical research design with a cross-sectional approach. The method used is quantitative, aiming to describe the knowledge regarding clean water management in Mahengetang Island. Results: The results indicate that the community's knowledge about water management in Mahengetang Island is mostly at a moderate level, with 33 households (48.93%) falling into this category. A minority of the community has low knowledge, with 19 households (26.02%). These findings align with research conducted by Muhammad Akbar Salca in the working area of the Tutar Health Center in Tutar District, Polewali Mandar in 2015, which revealed that out of 92 respondents, the majority had low knowledge (56 respondents, or 56.85%), while a minority had moderate knowledge (20 respondents, or 21.05%). Conclusion: Based on the findings of the study titled “Community Knowledge on Clean Water Management in Mahengetang Island, Sangihe Regency, 2023,” it can be concluded that a minority of respondents have low knowledge (19 households, or 26.02%), while the majority have moderate knowledge (33 households, or 48.93%), and 19 individuals (26.02%) possess good knowledge.